Is Cardiopulmonary Resuscitation Futile in Coronavirus Disease 2019 Patients Experiencing In-Hospital Cardiac Arrest?*. Issue 2 (February 2021) - Shah, Priyank; Smith, Hallie; Olarewaju, Ayodeji; Jani, Yash; Cobb, Abigail; Owens, Jack; Moore, Justin; Chenna, Avantika; Hess, David
Abstract : Objectives: There is limited data regarding outcomes after in-hospital cardiac arrest among coronavirus disease 2019 patients. None of the studies have reported the outcomes of in-hospital cardiac arrest in coronavirus disease 2019 patients in the United States. We describe the characteristics and outcomes of in-hospital cardiac arrest in coronavirus disease 2019 patients in rural Southwest Georgia. Design: Retrospective cohort study. Setting: Single-center, multihospital. PATIENTS: Consecutive coronavirus disease 2019 patients who experienced in-hospital cardiac arrest with attempted resuscitation. Interventions: Attempted resuscitation with advanced cardiac life support. Measurement and Main Results: Out of 1, 094 patients hospitalized for coronavirus disease 2019 during the study period, 63 patients suffered from in-hospital cardiac arrest with attempted resuscitation and were included in this study. The median age was 66 years, and 49.2% were males. The majority of patients were African Americans (90.5%). The most common comorbidities were hypertension (88.9%), obesity (69.8%), diabetes (60.3%), and chronic kidney disease (33.3%). Eighteen patients (28.9%) had a Charlson Comorbidity Index of 0–2. The most common presenting symptoms were shortness of breath (63.5%), fever (52.4%), and cough (46%). The median duration of symptoms prior to admission was 14 days. During hospital course, 66.7% patients developed septic shock, and 84.1% had acute respiratory distress syndrome. Prior to in-hospital cardiac arrest, 81% were on ventilator, 60.3% were on vasopressors, and 39.7% were on dialysis. The majority of in-hospital cardiac arrest (84.1%) occurred in the ICU. Time to initiation of advanced cardiac life support protocol was less than 1 minute for all in-hospital cardiac arrest in the ICU and less than 2 minutes for the remaining patients. The most common initial rhythms were pulseless electrical activity (58.7%) and asystole (33.3%). Although return of spontaneous circulation was achieved in 29% patients, it was brief in all of them. The in-hospital mortality was 100%. Conclusions: In our study, coronavirus disease 2019 patients suffering from in-hospital cardiac arrest had 100% in-hospital mortality regardless of the baseline comorbidities, presenting illness severity, and location of arrest.